O możliwości zredefiniowania niepowodzeń szkolnych. Rekonstrukcja zmiany myślenia studentek – przyszłych nauczycielek wczesnej edukacji - Grażyna Szyling (Problemy Wczesnej Edukacji)
The aim of the article of to identify the scope of early education students redefining the concept of school failures considered in the contexts of paradigmatic view on didactics and the issue of educating professional teachers. I subject to analysis fragments of students portfolio, which I treat as desk data. For this purpose I employ the method of qualitative analysis of text. The results of the analyses show that the most significant modification concerns inclusion into the area of school failures also students commonly regarded as those „not having learning difficulties”, which extends the definition of this notion with the sense of “being insufficient” and leads to, inter alia, the relativisation of the term “bad grade”. Into the set of temporally remote effects of experiencing school failures the students include predominantly the inability to undertake an independent cognitive search in a situation when the exemplary right answer is not provided. Identifying – as constructivists have done – school failures as the failures of the school, the respondents locate the sources of this phenomenon in the dominance of the traditional model of objectivist school, and in particular – in multiple symptoms of the cult of average grade and thoughtless realisation of the curriculum by teachers. The text also show the effects of the possibility of educating teachers open to the complexity of Educational reality and ready for a theoretically deep insight into their own school experience.